Genetic diversity of 12 X-chromosomal short tandem repeats in Jewish populations. (December 2015) - Ferragut, J.F.; Castro, J.A.; Ramon, C.; Picornell, A.
Abstract: Haplotype and allele frequencies of 12 X-STRs included in the Investigator Argus X-12 kit were studied for 313 individuals, representing five populations with known Jewish ancestry. The high efficiency in forensic parameters in all the populations studied demonstrates that this set of markers provides a powerful tool for solving complex kinship cases in Jewish populations.